ASPECTS REGARDING INTERNATIONAL RESPONSIBILITY BY ANALYSING THE AGENCY RELATIONSHIP BETWEEN THE INTERNATIONAL ORGANIZATION AND THE STATE - Ovidiu-Emilian IVĂNESCU (Challenges of the Knowledge Society)
The study analyses the consequences for the responsibility of the organization and the relevant state of an agency relationship between an international organization acting as a principal and a state acting as its agent. It is prouved that an international organization may be responsible for damage caused by the conduct of the state. We can also sustain that the state itself may bear responsability for having established or for not having terminated the agency relationship if it commits wrongful conduct on behalf of the international organization.